Fear of childbirth and psychiatric disorders decrease the likelihood of subsequent births: a retrospective register-based cohort study - Silvan, Elina; Saisto, Terhi; Mäkelä, Tia; Salmela-Aro, Katariina; Gissler, Mika; Lampio, Laura (Springer Science and Business Media LLC, 2025)
Background
Mirroring other developed countries globally, the birth rate has decreased in Finland in recent years. The effects of a fear of childbirth (FOC) and psychiatric disorders on the likelihood of having more than one child remain relatively unstudied. This study aims to assess the influence of FOC, psychiatric disorders, and the mode of first delivery on the likelihood of the second birth among primiparous women.
Methods
Data were collected from the Medical Birth Register, the Hospital Discharge Register, and Statistics Finland census data. We used the t-test to compare continuous variables and the chi-square test or test for relative proportions to compare categorical variables. We calculated the hazard ratios (HRs) and 95% confidence intervals (CIs) using the Cox regression analysis.
Results
Altogether, 317 219 women delivering their first child in 2006–2016 met the inclusion criteria, 216 521 of whom (68.3%) had their second birth during that time. A total of 11 108 (3.5%) of women were diagnosed with FOC during their first pregnancy, 34 381 (10.8%) women were diagnosed with a psychiatric disorder before or during their first pregnancy and 10 331 (3.3%) women received a new diagnosis of a psychiatric condition following the first birth. Between 2006–2021, the second child was born to 47.5% of women with FOC (n = 5276), 56.8% of women with a psychiatric disorder before or during their first pregnancy (n = 19 540), 53.4% of women receiving a psychiatric diagnosis after their first delivery (n = 5514) and 70.2% of women without either of these diagnoses (n = 191 572). Women with FOC had a 22% lower likelihood of the second birth [aHR 0.78 (95% CI 0.76–0.80)] compared to women without FOC. A psychiatric disorder before or during the first pregnancy decreased the likelihood of the second birth by 28% [aHR 0.72 (95% CI 0.71–0.73)] and by 51% (aHR 0.49 (95% CI 0.48–0.50)] with a psychiatric disorder following a first birth compared with women without a diagnosed psychiatric disorder. Among all women, a caesarean section as the mode of a first delivery reduced the likelihood of the second birth.
Conclusion
FOC and psychiatric disorders are associated with a low birthrate following the first delivery. Caesarean section as the mode of delivery decreases the likelihood of the second birth among women with FOC and psychiatric disorders.